Neuropsychological aspects of the patient’s personality in the context of psychosomatic experience - Krause, Robert; Forgon, Tomáš (Frontiers in Psychiatry, 2025)
The primary objective of this study was to examine the relationship between personal variables, as measured by the NEO-PI-R, and psychosomatic symptoms, assessed through the PSS, from a neuropsychological perspective. The secondary aim was to evaluate the frequency of various psychosomatic symptoms and assess the extent to which participants experience these symptoms. This online study included participants from across Slovakia (n = 222, M = 34.0, SD = 9.49). Participants completed the Big Five personality questionnaire (NEO-PI-R) and the Scale of Psychosomatic Symptoms (PSS). Analysis revealed significant relationships between conscientiousness and overall health perception (β=−1.19∗∗), with conscientiousness positively correlating with the intensity of pseudoneurological (β=.21∗∗), cardiovascular (β=.15∗), and musculoskeletal symptoms (β=.15∗). Neuroticism was significantly related to overall health perception (β=.19∗∗), problem frequency (β=−.19∗∗), and the extent of health-related suffering (β=−.15∗), as well as the frequency of respiratory (β=−.14∗) and gastrointestinal issues (β=−.16∗), pain-related problems (β=−.18∗∗), and the intensity of gastrointestinal symptoms (β=−.14∗). Extraversion, openness, and agreeableness did not show significant relationships with psychosomatic symptoms (p>0.05). The majority of participants (56%) did not seek medical attention, while 44% did. Seventy percent had no medical diagnosis, while 30% reported a diagnosis from a healthcare professional. The most frequently reported symptoms were fatigue (M=2.69,SD=0.835) and back pain (M=2.32,SD=0.950).